Cancer stem cells: advances in biology and clinical translation—a Keystone Symposia report. Issue 1 (30th November 2021) - Cable, Jennifer; Pei, Duanqing; Reid, Lola M.; Wang, Xin Wei; Bhatia, Sonam; Karras, Panagiotis; Melenhorst, Jan Joseph; Grompe, Markus; Lathia, Justin D.; Song, Erwei; Kuo, Calvin J.; Zhang, Ning; et al.
Abstract: The test for the cancer stem cell (CSC) hypothesis is to find a target expressed on all, and only CSCs in a patient tumor, then eliminate all cells with that target that eliminates the cancer. That test has not yet been achieved, but CSC diagnostics and targets found on CSCs and some other cells have resulted in a few clinically relevant therapies. However, it has become apparent that eliminating the subset of tumor cells characterized by self‐renewal properties is essential for long‐term tumor control. CSCs are able to regenerate and initiate tumor growth, recapitulating the heterogeneity present in the tumor before treatment. As great progress has been made in identifying and elucidating the biology of CSCs as well as their interactions with the tumor microenvironment, the time seems ripe for novel therapeutic strategies that target CSCs to find clinical applicability. On May 19–21, 2021, researchers in cancer stem cells met virtually for the Keystone eSymposium "Cancer Stem Cells: Advances in Biology and Clinical Translation" to discuss recent advances in the understanding of CSCs as well as clinical efforts to target these populations. Abstract : Cancer stem cells (CSC) comprise a small population of tumor cells with self‐renewing potential and are resistant to many conventional cancer therapies that target highly proliferating cells. Great strides have been made in identifying and elucidating the biology of CSCs in many tumors and their microenvironments. Novel therapeutic strategies that target CSCs and cancer cell heterogeneity and plasticity are rapidly progressing to the clinical arena. On Demand content : https://keysym.us/21EK46NYAS .